On the taxonomic identity of Brachistosternus peruvianus Piza, 1974 (Scorpiones: Bothriuridae) - Ochoa, José A. (2011)
The true identity of Brachistosternus peruvianus Piza, 1974, a controversial Andean scorpion previously confused with Brachistosternus andinus Chamberlin, 1916, is established. Both species inhabit inter Andean valleys of southern Peru and belong to the subgenus Brachistosternus (Ministernus) Francke. A detailed redescription of both species based on external morphology, pigmentation pattern and hemispermatophore features are provided. New records for these species, along with brief discussions of the ecology and distribution are also reported.